Organic Fertilizer Application of Shrimp Pond Waste Sediment For Growth And Productivity (Lactuca Sativa Crispa L ) - Adha Sabila Kifah; Agus Sutanto; Hening Widowati; Muhfahroyin Muhfahroyin (Jurnal Penelitian Pertanian Terapan, 2020)
Curly lettuce is one of the types of vegetables favoured by the community, but lately, organic vegetables are more in demand. One effort to get organic vegetables by using organic fertilizer during the planting period. Organic fertilizers come from nature, one of which is shrimp pond sediment whose utilization is not optimal. This study aims to determine the effect of shrimp pond sediment organic fertilizer application for growth and productivity of curly lettuce (Lactuca sativa cispa L). The study was conducted for 40 days, this type of research experiments using a Completely Randomized Design (CRD) with 4 treatments and 1 control and 6 replications. The parameters used include plant height and wet weight of curly lettuce plants. The main data is tabulated and analyzed using the SPSS 16.0 application which includes Multivariate Analysis of Variance (MANOVA). It was concluded that the organic fertilizer of shrimp pond sediment variation P1 (the composition of 100% shrimp pond sediment) provided the most optimal effect on the growth and productivity of curly lettuce (Lactuca sativa crispa L). Brochure validation results indicate that the brochure is very suitable to be used as a source of information about pond organic sediment fertilizer.